Penolakan Kurban dalam Amos 5:21-27 dan Relevansinya dengan Sila Kelima Pancasila - Helda Sriwijayati; Timothy Uriel Pelmar; Sandro Hasoloan L Tobing (Sekolah Tinggi Teologi Torsina Surakarta, 2022)
Amos 5:21-27 shows the Israelite sacrifice being rejected by God, even though the sacrifice fulfilled the ritual requirements. The people of Israel in the time of Amos were required by God to do justice and righteousness, but they did not do so, and the Lord sentenced them. Some scholars also argue about this rejection, and they fall into two groups. The first group concludes that God rejected the sacrifice because He did not need it. The second group believes that sacrifice is needed but must be followed by people living based on justice and righteousness. The Israelite people during Amos's time ignored justice; corruption, economic inequality, and poverty were rampant. Even though its people are religious, Indonesia also has serious social injustice problems. The poverty rate is high, economic inequality is wide, and corruption is easy to find. The interpretation of Amos 5:21-27 about justice is relevant to Pancasila, especially the fifth principle,